Servant leadership and project success: the mediating roles of team learning orientation and team agility - Han, Huibin; Zhang, Xiaojia (Frontiers in Psychology, 2024)
Drawing from social learning theory, this study aims to explore the mediating effects of team learning orientation and team agility on the relationship between servant leadership and project success in the context of construction projects. Based on data collected from 306 construction project members in China, the findings reveal that servant leadership exerts a positive influence on project success. Additionally, servant leadership significantly enhances both team learning orientation and team agility, which in turn contribute to project success. Furthermore, the results demonstrate the serial and parallel mediating roles of team learning orientation and team agility between servant leadership and project success. Theoretical and practical implications were also provided based on the findings.